COMMUNICATION OF WOMEN'S PARTICIPATION IN THE PRESERVATION AND MANAGEMENT OF SUSTAINABLE FOREST RESOURCES IN TAHURA WAR LAMPUNG PROVINCE INDONESIA - Fajar Sasora; Titi Widaningsih; Marlinda Irwanti (Bajang Institute, 2024)
The massive collection of non-timber forest products has led to around 80% of the land in Wan Abdul Rachman Forest Park (Tahura WAR) being controlled by the community. This has resulted in an increase in the rate of deforestation and damage to the forest canopy. Forest sustainability is one of the unresolved problems throughout Indonesia, the rate of forest destruction is higher than the preservation or planting of trees. Likewise in Lampung Province, the basic problem is the increasing population growth so that there are needs that must be met, while the availability of land does not increase. However, ecological impacts are not the only aspect of concern. Related to this, gender issues are also a serious concern in the context of agricultural and plantation expansion. Research has shown that there are significant gender differences in terms of dependence on forests for livelihoods and intended use of forest resources. Women in the KTH Tahura WAR have a role as those who do not directly benefit from the forest. Many women do not enter the forest and manage the land directly, but rather process a small portion of forest products into finished products with limited marketing. This research aims to analyse women's participatory communication in the preservation and management of sustainable forest resources in Tahura Wan Abdul Rachman, Lampung Province. The research method used in this study is qualitative ethnographic communication, which focuses more on social reality in the process of interaction between individuals in carrying out daily activities. The results showed the existence of participatory communication with four dimensions of participatory communication, namely heteroglasia, dialogue, polyponni, carnival. In the efforts to conserve and manage forest resources carried out by women around the forest, they have an important role as part of the non-timber forest product collection actors. Although women's participatory communication in the utilisation of forest resources is still minimal, researchers provide two important contexts to complement inclusive participatory communication, namely collaboration and cultural expression in forest resource manageme